Infomax and FASTICA using principle component analysis as preprocessor for airwave removal in seabed logging - Ansari, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
This research aims to apply the FASTICA and Infomax algorithm in the field of seabed logging, by utilizing the Principal Component Analysis (PCA) as preprocessor. All the three algorithms are statistical algorithms used for signal deconvolution and are respectively in the field of Independent Component Analysis (ICA). In seabed logging (SBL) implies the marine controlled source electromagnetic (CSEM) technique for the detection of hydrocarbons underneath the seabed floor. The results from SBL, indicate the presence of Hydrocarbon, but due to the presence of noise, in the form of airwaves, interfere with the signals from the subsurface and tend to dominate the receiver response. Hence, the Infomax and FASTICA de-convolution algorithms are used, considering PCA as a pre-processor to filter out the airwaves which disrupt the subsurface signals within the receiver response. The results obtained from simulations and their comparative analysis, indicate that the results from the infomax algorithm are better. Â© 2014 IEEE.